Prevalence and risk factors for metabolic syndrome in urban elderly: a community study from Tirupati, Chittoor district, Andhra Pradesh, India - Naik, J. Lalu; Reddy, K. S. N; Reddy, B. K. C; Basha, D. Anwar (International Journal Of Community Medicine And Public Health, 2017)
Background: Metabolic syndrome (MetS) is a major risk factor for the development of type 2 diabetes (T2D) and cardiovascular diseases (CVDs) in the elderly. Present study aimed to discuss the prevalence and risk factors of MetS in the urban elderly population of Tirupati, Chittoor district of Andhra Pradesh. Methods: A cross-sectional survey is conducted among elderly (aged 60 years and above). A total of 295 participants (males: 108; females: 187) are studied. MetS is defined using the modified adult treatment panel III (ATP III) criteria. Results: Of the study participants, 34.58% had MetS. Abnormalities in blood pressure, blood sugar, and waist circumference (WC) are the three most common risk factors. The odds ratio for MetS is higher with female sex, older age, and high body mass index (BMI) and lower with a higher education level. There are strong correlations found between BMI and WC, triglyceride and high-density lipoprotein cholesterol (HDL-C), and WC and HDL-C. Conclusions: The majority of the elderly population in Tirupati urban had at least two risk factors for MetS. Patient education and regular screening are needed for early detection and management of risk factors in order to prevent evolvement to MetS and related chronic diseases.